2015
DOI: 10.1021/es506065d
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Organic Ligands on Forsterite Reactivity in Supercritical CO2 Fluids

Abstract: Subsurface injection of CO2 for enhanced hydrocarbon recovery, hydraulic fracturing of unconventional reservoirs, and geologic carbon sequestration produces a complex geochemical setting in which CO2-dominated fluids containing dissolved water and organic compounds interact with rocks and minerals. The details of these reactions are relatively unknown and benefit from additional experimentally derived data. In this study, we utilized an in situ X-ray diffraction technique to examine the carbonation reactions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
75
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(90 citation statements)
references
References 112 publications
13
75
2
Order By: Relevance
“…In this present work, which is a continuation of the Miller et al [25] study, we performed additional experiments in order to accomplish four goals: 1) verify transport of simple organic ligands via solvation by scCO 2 , 2) further investigate the impacts that the organics have on magnesium carbonate precipitation in thin adsorbed water films, 3) attempt to determine the flux of citrate complexes to the forsterite surface in Miller et al [25], and 4) identify evidence of metal-organic partitioning into the water-saturated scCO 2 phase. The in situ spectroscopic experiment was conducted with a calcium acetate solution at similar conditions to EXP 2 in Miller et al [25].…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…In this present work, which is a continuation of the Miller et al [25] study, we performed additional experiments in order to accomplish four goals: 1) verify transport of simple organic ligands via solvation by scCO 2 , 2) further investigate the impacts that the organics have on magnesium carbonate precipitation in thin adsorbed water films, 3) attempt to determine the flux of citrate complexes to the forsterite surface in Miller et al [25], and 4) identify evidence of metal-organic partitioning into the water-saturated scCO 2 phase. The in situ spectroscopic experiment was conducted with a calcium acetate solution at similar conditions to EXP 2 in Miller et al [25].…”
Section: Introductionsupporting
confidence: 51%
“…In the subsurface, the injected scCO 2 produces regions in which the full spectrum of mutual CO 2 -H 2 O solubility can occur [6][7][8][9]. In basalt reservoirs, the CO 2 -rich (water-bearing scCO 2 ) fluids are highly reactive with regard to the minerals present [10], and the scCO 2 may mobilize the organics, as scCO 2 is an effective solvent of organic matter [11], which has been observed in the field and in experiments with geomaterials [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In our recent investigation, we demonstrated that simple, naturally abundant organic ligands (the protonated forms of acetate, malonate, oxalate, and citrate) were transported through water-saturated scCO 2 and their presence impacted the carbonation of forsterite [25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations